2020
DOI: 10.1371/journal.pone.0240815
|View full text |Cite
|
Sign up to set email alerts
|

A realist review of advance care planning for people with multiple sclerosis and their families

Abstract: Background Advance care planning (ACP) is reported to improve the quality of outcomes of care among those with life-limiting conditions. However, uptake is low among people living with multiple sclerosis (MS) and little is known about why or how people with MS engage in this process of decision-making. Aims To develop and refine an initial theory on engagement in ACP for people with MS and to identify ways to improve its uptake for those who desire it. Methods Realist review following published protocol and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 89 publications
(270 reference statements)
2
26
0
Order By: Relevance
“…This finding supports a recent realist review of the imperative for health professionals to engage with people with MS in the ACP process at the most opportune moment and that health professional be considered by the person with MS to have trusting and empathic qualities. 26 In addition, GPs were shown to subsequently take a role in coordinating future patient care together with their family and were instrumental in contributing to making it possible for that care to take place in a location of the patient's preference to prevent hospital deaths. This finding cannot be underestimated, particularly given that these instances of conversations and subsequent care were more frequent than among patients where ACP discussions were initiated by other HCPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding supports a recent realist review of the imperative for health professionals to engage with people with MS in the ACP process at the most opportune moment and that health professional be considered by the person with MS to have trusting and empathic qualities. 26 In addition, GPs were shown to subsequently take a role in coordinating future patient care together with their family and were instrumental in contributing to making it possible for that care to take place in a location of the patient's preference to prevent hospital deaths. This finding cannot be underestimated, particularly given that these instances of conversations and subsequent care were more frequent than among patients where ACP discussions were initiated by other HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings compel any initiative aimed at enabling people with neurological illnesses who express a desire to remain at home to respond adequately to all factors we identify in this study and also consider the contribution of ACP and the conditions required to make it relevant and acceptable to those who might benefit from it. 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A realist review identified two main barriers for ACP discussions taking place: the long and uncertain MS trajectory, with periods of stability punctuated by crisis; and lack of ACP communication skills and confidence of HPs. 23 ConCure-SM is a project aimed to set up and evaluate the efficacy of an ACP intervention for pwPMS in Italy. The Shared Decision Making model described earlier is the theoretical framework of the project.…”
Section: Open Accessmentioning
confidence: 99%
“… 22 A realist review identified two main barriers for ACP discussions taking place: the long and uncertain MS trajectory, with periods of stability punctuated by crisis; and lack of ACP communication skills and confidence of HPs. 23 …”
Section: Introductionmentioning
confidence: 99%